Comprehensive genomic characterization of hematologic malignancies at a pediatric tertiary care center - Kebede, Ann M.; Garfinkle, Elizabeth A. R.; Mathew, Mariam T.; Varga, Elizabeth; Colace, Susan I.; Wheeler, Gregory; Kelly, Benjamin J.; Schieffer, Kathleen M.; Miller, Katherine E.; Mardis, Elaine R.; Cottrell, Catherine E.; Potter, Samara L. (Frontiers in Oncology, 2024)
Despite the increasing availability of comprehensive next generation sequencing (NGS), its role in characterizing pediatric hematologic malignancies remains undefined. We describe findings from comprehensive genomic profiling of hematologic malignancies at a pediatric tertiary care center. Patients enrolled on a translational research protocol to aid in cancer diagnosis, prognostication, treatment, and detection of cancer predisposition. Disease-involved samples underwent exome and RNA sequencing and analysis for single nucleotide variation, insertion/deletions, copy number alteration, structural variation, fusions, and gene expression. Twenty-eight patients with hematologic malignancies were nominated between 2018-2021. Eighteen individuals received both germline and somatic sequencing; two received germline sequencing only. Germline testing identified patients with cancer predisposition syndromes and non-cancer carrier states. Fifteen patients (15/18, 83%) had cancer-relevant somatic findings. Potential therapeutic targets were identified in seven patients (7/18, 38.9%); three (3/7, 42.9%) received targeted therapies and remain in remission an average of 47 months later.